Pengembangan Label Pintar Pemantau Kematangan Buah Pepaya Potong Berbasis Indikator pH Methyl Red Dan Bromocresol Purple - Faizah oktaviana; Nia Kristinigrum; Dwi Koko Pratoko (UPT Percetakan dan Penerbitan Universitas Jember, 2022)
Papaya fruit is generally marketed in a condition not yet ripe until past ripe. During the ripening process, the fruit undergoes changes such as increased sugar levels, changes in texture, changes in color on the skin and flesh of the fruit, changes in the rate of CO2 and ethylene production. Papaya fruit is declared rotten if it has a pH below 5.2. Methyl red (MR) indicator changes from red to yellow in the pH range (4.4 - 6.2) and bromocresol purple (BCP) has a pH of 5.2 (yellow) and a pH of 6.8 (purple). Papaya fruit stored at room temperature began to show rot on the 4th day accompanied by a change in the color of the smart bromocresol purple label to yellow, methyl red to red decreased in weight loss of 6.5332%, pH 4.85, hardness of 69.833 g / mm, and total dissolved solids 9.88% brik. At the temperature of the papaya fruit chiller stored for 9 days has shown foul on the 7th day with the same smart label color as room temperature, a decrease in weight loss of 6.4645%, pH 4.95, hardness of 83g / mm, and total dissolved solids 9.67% brik. The faster the color change of the smart label, the lower the quality of papaya on the packaging so that the fruit is not suitable for consumption.